2017
DOI: 10.1371/journal.pone.0180292
|View full text |Cite
|
Sign up to set email alerts
|

Instruments for the assessment of suicide risk: A systematic review evaluating the certainty of the evidence

Abstract: BackgroundInstruments have been developed to facilitate suicide risk assessment. We aimed to evaluate the evidence for these instruments including assessment of risk of bias and diagnostic accuracy for suicide and suicide attempt.MethodsPubMed (NLM), PsycInfo, Embase, Cinahl and the Cochrane Library databases were searched until December 2014. We assessed risk of bias with QUADAS-2. The average sensitivity and specificity of each instrument was estimated and the certainty of the evidence was assessed with GRAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 55 publications
6
144
1
9
Order By: Relevance
“…A meta-analysis of five instruments across the studies showed that none of the instruments reached the predetermined benchmarks (80% sensitivity and 50% specificity) for the suicide outcome or suicide attempt outcome. With few exceptions, low figures were observed for the positive predictive value for the suicide outcome (1-13%) 83. This review, however, did not include the diagnostic accuracy of the Suicide Assessment Scale (SUAS) or the Columbia Suicide Severity Rating Scale (C-SSRS).…”
Section: Depression and Suicide Riskmentioning
confidence: 99%
“…A meta-analysis of five instruments across the studies showed that none of the instruments reached the predetermined benchmarks (80% sensitivity and 50% specificity) for the suicide outcome or suicide attempt outcome. With few exceptions, low figures were observed for the positive predictive value for the suicide outcome (1-13%) 83. This review, however, did not include the diagnostic accuracy of the Suicide Assessment Scale (SUAS) or the Columbia Suicide Severity Rating Scale (C-SSRS).…”
Section: Depression and Suicide Riskmentioning
confidence: 99%
“…However, this contradicts recommendations which suggest that locally developed risk assessment tools that lack an evidence base should be abandoned . Furthermore, recent findings show that the SAD PERSONS scale is not statistically reliable, and should not be used in its present form …”
Section: Introductionmentioning
confidence: 99%
“…Still, only a few countries have included suicide prevention among their health priorities, and only 28 countries report having a national suicide prevention strategy. So, even today, little is known about how to make proper suicide risk assessments (Runesson et al, ). MHPs with extensive experience can have expert knowledge, which is intuitive (Benner, ).…”
Section: Introductionmentioning
confidence: 99%